Novel bio-spectroscopic imaging reveals disturbed protein homeostasis and thiol redox with protein aggregation prior to hippocampal CA1 pyramidal neuron death induced by global brain ischemia in the rat - Hackett, Mark; Smith, S.; Caine, S.; Nichol, H.; George, G.; Pickering, I.; Paterson, P. (Elsevier, 2015)
Global brain ischemia resulting from cardiac arrest and cardiac surgery can lead to permanent brain damage and mental impairment. A clinical hallmark of global brain ischemia is delayed neurodegeneration, particularly within the CA1 subsector of the hippocampus. Unfortunately, the biochemical mechanisms have not been fully elucidated, hindering optimization of current therapies (i.e., therapeutic hypothermia) or development of new therapies. A major limitation to elucidating the mechanisms that contribute to neurodegeneration and understanding how these are influenced by potential therapies is the inability to relate biochemical markers to alterations in the morphology of individual neurons. Although immunocytochemistry allows imaging of numerous biochemical markers at the sub-cellular level, it is not a direct chemical imaging technique and requires successful "tagging" of the desired analyte. Consequently, important biochemical parameters, particularly those that manifest from oxidative damage to biological molecules, such as aggregated protein levels, have been notoriously difficult to image at the cellular or sub-cellular level. It has been hypothesized that reactive oxygen species (ROS) generated during ischemia and reperfusion facilitate protein aggregation, impairing neuronal protein homeostasis (i.e., decreasing protein synthesis) that in turn promotes neurodegeneration. Despite indirect evidence for this theory, direct measurements of morphology and ROS induced biochemical damage, such as increased protein aggregates and decreased protein synthesis, within the same neuron is lacking, due to the unavailability of a suitable imaging method. Our experimental approach has incorporated routine histology with novel wide-field synchrotron radiation Fourier transform infrared imaging (FTIRI) of the same neurons, ex vivo within brain tissue sections. The results demonstrate for the first time that increased protein aggregation and decreased levels of total protein occur in the same CA1 pyramidal neurons 1 day after global ischemia. Further, analysis of serial tissue sections using X-ray absorption spectroscopy at the sulfur K-edge has revealed that CA1 pyramidal neurons have increased disulfide levels, a direct indicator of oxidative stress, at this time point. These changes at 1 day after ischemia precede a massive increase in aggregated protein and disulfide levels concomitant with loss of neuron integrity 2 days after ischemia. Therefore, this study has provided direct support for a correlative mechanistic link in both spatial and temporal domains between oxidative stress, protein aggregation and altered protein homeostasis prior to irreparable neuron damage following global ischemia. © 2015 Elsevier Inc. All rights reserved.